Pharmaceutical Assessment Suggests Locomotion Hyperactivity in Zebrafish Triggered by Arecoline Might Be Associated with Multiple Muscarinic Acetylcholine Receptors Activation - Siregar, Petrus; Audira, Gilbert; Feng, Ling-Yi; Lee, Jia-Hau; Santoso, Fiorency; Yu, Wen-Hao; Lai, Yu-Heng; Li, Jih-Heng; Lin, Ying-Ting; Chen, Jung-Ren; Hsiao, Chung-Der (Toxins, 2021)
Arecoline is one of the nicotinic acid-based alkaloids, which is found in the betel nut. In addition to its function as a muscarinic agonist, arecoline exhibits several adverse effects, such as inducing growth retardation and causing developmental defects in animal embryos, including zebrafish, chicken, and mice. In this study, we aimed to study the potential adverse effects of waterborne arecoline exposure on zebrafish larvae locomotor activity and investigate the possible mechanism of the arecoline effects in zebrafish behavior. The zebrafish behavior analysis, together with molecular docking and the antagonist co-exposure experiment using muscarinic acetylcholine receptor antagonists were conducted. Zebrafish larvae aged 96 h post-fertilization (hpf) were exposed to different concentrations (0.001, 0.01, 0.1, and 1 ppm) of arecoline for 30 min and 24 h, respectively, to find out the effect of arecoline in different time exposures. Locomotor activities were measured and quantified at 120 hpf. The results showed that arecoline caused zebrafish larvae locomotor hyperactivities, even at a very low concentration. For the mechanistic study, we conducted a structure-based molecular docking simulation and antagonist co-exposure experiment to explore the potential interactions between arecoline and eight subtypes, namely, M1a, M2a, M2b, M3a, M3b, M4a, M5a, and M5b, of zebrafish endogenous muscarinic acetylcholine receptors (mAChRs). Arecoline was predicted to show a strong binding affinity to most of the subtypes. We also discovered that the locomotion hyperactivity phenotypes triggered by arecoline could be rescued by co-incubating it with M1 to M4 mAChR antagonists. Taken together, by a pharmacological approach, we demonstrated that arecoline functions as a highly potent hyperactivity-stimulating compound in zebrafish that is mediated by multiple muscarinic acetylcholine receptors.